An interval-estimation-based anti-disturbance sliding mode control strategy for rigid satellite with prescribed performance. (October 2020) - Zhou, Zepeng; Zhu, Fanglai; Xu, Dezhi; Gao, Zhifeng
Abstract: This paper investigates an anti-disturbance sliding mode control strategy for a rigid satellite system with external disturbance under the prescribed performance constraints. An interval observer is firstly introduced to generate the interval estimation of the attitude angular velocity. Then a finite time identical disturbance reconstruction strategy is developed by using the interval estimation. Based on the novel performance function and error transformation constraints, the attitude tracking error is converted into a new error system that guarantees the desired transient and steady-state responses for the tracking error. Then, by introducing the reconstructed disturbance, a finite time anti-disturbance controller is constructed with the backstepping method. The stability of the strategy is guaranteed by the Lyapunov stability method. Finally, simulation results demonstrate the effectiveness of the proposed approach. Highlights: Proposed an interval observer for the rigid satellite attitude system. Proposed an interval-estimation-based identical disturbance reconstruction method. Proposed a finite time backstepping prescribed performance controller for the system.